Gambaran Kadar Elektrolit Darah Pada Pasien Diare Akut di Rumah Sakit Tk. II M. Ridwan Meuraksa Jakarta - Kamaliyah, Saffanah Hayya; Rahayu, Cahyawati; Nurdiani, Catu Umirestu; Kristianingsih, Yuli; Nugroho, Heru Purwanto (Universitas Mohammad Husni Thamrin, 2025)
Diarrhea is a major health problem in Indonesia with the risk of dehydration and electrolyte imbalance. Electrolytes play an important role in maintaining the balance of fluids, acids-bases, as well as nerve and muscle function. This study aims to determine the overview of serum electrolyte levels (Na⁺, K⁺, Cl⁻) in patients with acute diarrhea in kindergarten hospitals. II M. Ridwan Meuraksa. This descriptive study used secondary data from the medical records of 157 patients with acute diarrhea. The laboratory examination uses the Ion Selective Electrode (ISE) method. The results showed that hyponatremia occurred in 40.6% of adult patients and 37.7% of elderly patients. Hypokalemia was found in 39.5% of adult patients and 31.1% of elderly patients. Chloride disorders were also significant, with 32.2% hypochloremia and 25% hyperchloremia in adults, and 37.7% hypochloremia and 34.4% hyperchloremia in the elderly. In conclusion, most patients with acute diarrhea experience electrolyte imbalances, especially hyponatremia and hypochloremia. Regular electrolyte checks are necessary in the treatment of diarrhea to prevent complications such as cardiac arrhythmias and kidney dysfunction. Keywords: Acute Diarrhea, Blood Electrolytes, Sodium, Potassium, Chloride.